Long‐term favorable prognosis in late onset dominant distal titinopathy: Tibial muscular dystrophy. (8th February 2023) - Lillback, Victoria; Savarese, Marco; Sandholm, Niina; Hackman, Peter; Udd, Bjarne
Abstract: Background and purpose: Tibial muscular dystrophy (TMD) is a dominant late onset distal titinopathy. It was first described in Finnish patients 3 decades ago. TMD patients with several other TTN mutations occur in many European populations. In this retrospective study, we were able to obtain longitudinal follow‐up data of the disease progression over 15 years in 137 TMD patients. Methods: We retrieved clinical data retrospectively from three examinations spanning a period of 15 years. The data were analyzed in R. Frequencies, percentages, and median values were used to describe data. Probability values were determined with the chi‐squared test. Results: In the cohort, the first symptoms were walking difficulties (97.8%) and weakness in distal lower limbs (98.5%). The progression of the weakness in distal lower limbs was moderate, and in the proximal lower limbs and proximal upper limbs it was mild. The distal upper limbs were not affected. Magnetic resonance imaging results indicated fatty degeneration preferentially in lower leg anterior muscles, gluteus minimus, and hamstring muscles. Serum creatine kinase values in the cohort were mostly normal (40.7%) or mildly elevated (53.7%). The data suggest that 50% of patients need walking aids by the age of 88 years. Conclusions: Despite individual variability of severity, the overall disability due to walking difficulties and upper limb weakness remained moderate even at very advanced ages, and cardiomyopathy did not develop due to the titin defect alone. The acquired results promote the correct identification of TMD, and the obtained trajectories of disease evolution can be used as natural history data for any therapeutic intervention. Abstract : We have retrospectively analyzed data from 137 patients with tibial muscular dystrophy, characterizing the disease and its natural history, enabling the diagnosis of the disease internationally, and providing data for any therapeutic intervention.